Effect of Levetiracetam Use Duration on Overall Survival of Isocitrate Dehydrogenase Wild-Type Glioblastoma in Adults: An Observational Study. (11th January 2022) - Pallud, Johan; Huberfeld, Gilles; Dezamis, Edouard; Peeters, Sophie; Moiraghi, Alessandro; Gavaret, Martine; Guinard, Eléonore; Dhermain, Frédéric; Varlet, Pascale; Oppenheim, Catherine; Chrétien, Fabrice; Roux, Alexandre; et al.
Abstract : Background and Objectives: The association between levetiracetam and survival with isocitrate dehydrogenase ( IDH ) wild-type glioblastomas is controversial. We investigated whether the duration of levetiracetam use during the standard chemoradiation protocol affects overall survival (OS) of patients with IDH wild-type glioblastoma. Methods: In this observational single-institution cohort study (2010–2018), inclusion criteria were (1) age ≥18 years; (2) newly diagnosed supratentorial tumor; (3) histomolecular diagnosis of IDH wild-type glioblastoma; and (4) standard chemoradiation protocol. To assess the survival benefit of levetiracetam use during the standard chemoradiation protocol (whole duration, part time, and never subgroups), a Cox proportional hazard model was constructed. We performed a case-matched analysis (1:1) between patients with levetiracetam use during the whole duration of the standard chemoradiation protocol and patients with levetiracetam use part time or never according to the following criteria: sex, age, epileptic seizures at diagnosis, Radiation Therapy Oncology Group recursive partitioning analysis (RTOG-RPA) class, tumor location, preoperative volume, extent of resection, and O6-methylguanine-DNA methyltransferase ( MGMT ) promoter methylation status. Patients with unavailable O6-methylguanine-DNA methyltransferase promoter methylation status (48.5%) were excluded. Results: A total of 460 patients were included. The median OS was longer in the 116 patients with levetiracetam use during the whole duration of the standard chemoradiation protocol (21.0 months; 95% confidence interval [CI] 17.2–24.0) than in the 126 patients with part-time levetiracetam use (16.8 months; 95% CI 12.4–19.0) and in the 218 patients who never received levetiracetam (16.0 months; 95% CI 15.5–19.4; p = 0.027). Levetiracetam use during the whole duration of the standard chemoradiation protocol (adjusted hazard ratio [aHR] 0.69; 95% CI 0.52–0.93; p = 0.014), MGMT promoter methylation (aHR 0.53; 95% CI 0.39–0.71; p < 0.001), and gross total tumor resection (aHR 0.57; 95% CI 0.44–0.74; p < 0.001) were independent predictors of longer OS. After case matching (n = 54 per group), a longer OS was found for levetiracetam use during the whole duration of the standard chemoradiation protocol (hazard ratio 0.63; 95% CI 0.42–0.94; p = 0.023). Discussion: Levetiracetam use during the whole standard chemoradiation protocol possibly improves OS of patients with IDH wild-type glioblastoma. It should be considered in the antitumor strategy of future multicentric trials. Classification of Evidence: This study provides Class III evidence that in individuals with IDH wild-type glioblastoma, levetiracetam use throughout the duration of standard chemotherapy is associated with longer median OS.